2020
DOI: 10.3389/fneur.2020.00594
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Puberty in Girls on Prevalence of Primary Headache Disorder Among Female Schoolchildren in Kuwait

Abstract: Background: The prevalence of primary headaches in the pediatric population is shaped by many factors, of which pubertal status may possibly play a substantial role. Epidemiological studies in the pediatric population in the gulf region remain scarce. Aims and objectives: To examine the impact of puberty on the prevalence of primary headache disorders among female schoolchildren in Kuwait. Methods: We conducted a cross-sectional study that included Kuwaiti primary and middle schoolgirls in randomly selected sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…Headaches were reported more frequently among middle schoolers compared to primary schoolers in our study (p = 0.001), a finding that applied to both genders (32) and was also observed in our previous epidemiological study (15). In further support of our findings, epidemiologic cross-sectional (27,32,33) and longitudinal (34) studies show that the prevalence of headaches increases with age.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Headaches were reported more frequently among middle schoolers compared to primary schoolers in our study (p = 0.001), a finding that applied to both genders (32) and was also observed in our previous epidemiological study (15). In further support of our findings, epidemiologic cross-sectional (27,32,33) and longitudinal (34) studies show that the prevalence of headaches increases with age.…”
Section: Discussionsupporting
confidence: 91%
“…This was reiterated by Zwart et al (26), Mehta (24), and our community-based epidemiological study (15), where we found a significantly higher prevalence of headaches among girls. More prevalence of primary headache in girls among middle schoolers could be explained by puberty and female sex hormones (27).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Further, uncorrected vision problems in combination with increased academic demands, may explain the increased prevalence of laboured reading and upper body musculoskeletal pain in the children who did not wear their recommended glasses/contact lenses (12 girls (11 in 10 th grade), 5 boys (4 in 10 th grade)) [ 77 ]. Increased frequency of pain symptoms in girls compared with boys, has previously been linked to differences in physiology and hormone profiles, and psychosocial factors [ 35 , 81 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Spreading cortical depression, which was previously pondered exclusively take place in migraines with aura, now appears to be present in all migraines (8). Central pain pathways are triggered by persistent nociceptive activation of the pericranial my fascia, which can be the cause of chronic tension-type headache conversion (9).…”
Section: Primary Headache's Neurochemistrymentioning
confidence: 98%